A practical nomogram based on serum interleukin-6 for the prognosis of liver failure - Xiao, Nanxi; Liu, Linxiang; Zhang, Yue; Nie, Yuan; Zhu, Xuan (Frontiers in Medicine, 2022)
Background Liver failure (LF) is a serious liver function damage caused by various factors, mainly jaundice, hepatic encephalopathy, coagulation disorders and multiple organ failure, with the clinical characteristic of high short-term mortality. LF is often accompanied by excessive activation of inflammatory factors, and an excessive systemic inflammatory response (i.e., inflammatory storm) is considered to be the trigger of LF. However, a specific prognostic model including inflammatory factors for patients with LF has not been well established. Aim  To establish and validate a nomogram for predicting 28-day, 90-day and 180-day mortality in patients with LF. Methods  A total of 423 eligible LF patients were enrolled in this retrospective study. Independent predictors were identified using a multivariate logistic model and then integrated into a nomogram to predict 28-day, 90-day, and 180-day mortality. The concordance index, receiver operating characteristic curves, and calibration plots were used to evaluate the performance of the model. Results Sex, age, total bilirubin, aspartate aminotransferase, international normalized ratio, Child–Pugh score and serum interleukin-6 were independent risk factors for death at 28, 90 and 180 days in LF patients. The nomogram showed good calibration and discrimination with an area under the receiver operating characteristic curve (AUC) of 0.927.The calibration curve fit as well, indicating that the nomogram had good clinical application value. Conclusion  This nomogram model for predicting the 28-day, 90-day, and 180-day mortality of LF patients could help optimize treatment strategies and improve prognosis.